2016
DOI: 10.1002/adfm.201505571
|View full text |Cite
|
Sign up to set email alerts
|

Monolayer MoS2 Dendrites on a Symmetry‐Disparate SrTiO3 (001) Substrate: Formation Mechanism and Interface Interaction

Abstract: Dendritic patterns mediated by non-equilibrium growth processes are ubiquitous in all length scales from atomic metal islands [ 1 ] to macroscopic snowfl akes. [ 2 ] These fractal species have attracted great research interests regarding their complex morphologies, unique formation mechanisms, [ 3 ] and more importantly intriguing physical and chemical properties. [ 4 ] A model fractal growth system toward these is metal-on-metal epitaxy [ 5 ] which is usually mediated by a limited diffusion of adatoms alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 39 publications
(23 reference statements)
4
64
0
Order By: Relevance
“…In other words, the growth results can be modulated by utilizing different growth substrates. Therefore, for a deep exploration of the formation mechanism, Zhang et al investigated the growth behavior of dendritic MoS 2 on STO(100) via experimental characterizations and theoretical calculations . Through a standard box‐counting evolution, Figure i presents statistics on the fractal dimensions ( D ) of a series dendritic flakes with an average D of 1.65 ± 0.08 (30 flakes; the left inset is a typical SEM image, and a linear fitting of the fractal dimensions is shown in the right inset of Figure i).…”
Section: D Semiconducting Tmdsmentioning
confidence: 99%
“…In other words, the growth results can be modulated by utilizing different growth substrates. Therefore, for a deep exploration of the formation mechanism, Zhang et al investigated the growth behavior of dendritic MoS 2 on STO(100) via experimental characterizations and theoretical calculations . Through a standard box‐counting evolution, Figure i presents statistics on the fractal dimensions ( D ) of a series dendritic flakes with an average D of 1.65 ± 0.08 (30 flakes; the left inset is a typical SEM image, and a linear fitting of the fractal dimensions is shown in the right inset of Figure i).…”
Section: D Semiconducting Tmdsmentioning
confidence: 99%
“…The fractal-shaped monolayer MoS 2 may find application in sensing, energy storage and transparent optoelectronics, etc. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 6 / 24 probably mediated by a relatively strong interface interaction and a diffusion-limited-aggregation (DLA) process [31][32] because of the ad-layer-substrate symmetry disparity. Briefly, in the DLA model, adatoms have to hop among predefined lattice sites of a substrate to achieve efficient bonding.…”
Section: Introductionmentioning
confidence: 98%
“…[46,47,108] For example, Zhang and colleagues recently reported a unique dendritic growth of monolayer MoS 2 on STO (001) (Figure 3a). [46,47] The MoS 2 dendrites were featured with fractal dimension of ≈1.6 which gradually increased to ≈2 for full coverage MoS 2 (Figure 3b), This was considered to obey a diffusion-limited aggregation (DLA) mechanism. DFT calculations subsequently revealed a prominent diffusion anisotropy of monomer MoS x precursors on STO (001) (Figure 3c,d).…”
Section: (4 Of 24)mentioning
confidence: 97%
“…[38][39][40][41][42][43][44][45][46][47] Particularly, their ultraflat surfaces, along with different interfacial energetics, and possible lattice registry to MX 2 adlayer, enabled additional controllability in a van der Waals epitaxy regime, leading to the formation of largely aligned monolayer domains or uniform complete layers. Liu et al, previously reported on the suitability of fluorophlogopite mica (KMg 3 AlSi 3 O 10 F 2 ) as a substrate for the van der Waals epitaxial growth of monolayer MoS 2 .…”
Section: Cvd Synthesis Of Monolayer MX 2 On Insulating Substratesmentioning
confidence: 99%
See 1 more Smart Citation